On some problems with nonlocal integral condition - Sergejeva, Natalija (Mathematical Modelling and Analysis, 2010)
We study the second order nonlinear boundary value problems with non‐local integral conditions and construct the Fučík type spectrum for these problems. First published online: 09 Jun 2011